Early childhood development when second-trimester ultrasound dating disagrees with last menstrual period: a prospective cohort study - Grewal Jagteshwar; Wernicke Meghan; Zhang Jun (BMC, 2012)
Abstract Background When an ultrasound-based estimate of gestational age (GA) is less (greater) than an estimate based on a definite last menstrual period, the fetus may grow slower (faster) than average. While the association between these discrepancies in GA estimates and adverse perinatal outcomes has been examined extensively, there is scant evidence about long-term effects, such as child neurodevelopment. Methods Using data from a prospective cohort study titled, NICHD Study of Successive Small-for-Gestational Age Births, we examined if GA discrepancies in early second trimester of pregnancy (17 weeks' gestation) are associated with: (1) impaired motor and mental function at 13 months (measured using Bayley Scales of Infant Development (Bayley)), and (2) impaired cognitive development at five years (assessed by Wechsler Preschool and Primary Scale of Intelligence - Revised Intelligence Quotient (WPPSI-R)) in the infant. The study population consisted of 572 (30% of the overall sample of 1,945) women who presented for prenatal care in Norway and Sweden between 1986 and 1988. Results Our results showed that GA discrepancies in early second trimester are significantly associated with birthweight. We found no significant relationship, however, with the Bayley development scores at 13 months and with the WPPSI-R IQ measures at five years. Conclusions GA discrepancies at 17 weeks' gestation are not associated child neurodevelopment. These discrepancies do, however, relate to birthweights, providing a basis for detecting fetal growth patterns early in the second trimester of pregnancy. Our study, however, was unable to evaluate the impact of first-trimester discrepancies on impaired neurodevelopment in the infant.